2016
DOI: 10.1186/s12875-016-0465-4
|View full text |Cite
|
Sign up to set email alerts
|

Urine sampling techniques in symptomatic primary-care patients: a diagnostic accuracy review

Abstract: BackgroundChoice of urine sampling technique in urinary tract infection may impact diagnostic accuracy and thus lead to possible over- or undertreatment. Currently no evidencebased consensus exists regarding correct sampling technique of urine from women with symptoms of urinary tract infection in primary care. The aim of this study was to determine the accuracy of urine culture from different sampling-techniques in symptomatic non-pregnant women in primary care.MethodsA systematic review was conducted by sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Urine reagent dipsticks have a low sensitivity and high specificity for the exclusion and identification of UTIs 77 · 78 , respectively. Formal microscopy, culture and antibiotic sensitivity (MCS) analyses of a clean-catch urine specimen or catheter urine specimen are recommended 79 in women who have symptoms of UTI or have a positive dipstick 63 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Urine reagent dipsticks have a low sensitivity and high specificity for the exclusion and identification of UTIs 77 · 78 , respectively. Formal microscopy, culture and antibiotic sensitivity (MCS) analyses of a clean-catch urine specimen or catheter urine specimen are recommended 79 in women who have symptoms of UTI or have a positive dipstick 63 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Urine was collected from 6 human patients who had given their written consent, in accordance with the ethics protocol of the collecting hospital, the County Emergency Hospital Cluj-Napoca, Romania (SCJU). The inclusion criteria were age above 18 years and the presence of clear clinical signs of UTI: hypogastric pain or/and dysuria or/and pollakiuria or/and disturbed urine or/and renal colic [ 66 ]. The exclusion criteria were antibiotic treatments 48 h previous to sampling and absence of leucocytes and/or of nitrites on dipstick analysis [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Past studies have shown mixed results when comparing clean catch and catheterized specimens. A systematic review article found that the lower specificity of voided samples would cause 5‐10% of patients to be overdiagnosed . In our study, we found that less than half of our cohort had a positive catheterized specimen despite having a positive clean catch.…”
Section: Discussionmentioning
confidence: 52%
“…In addition to infection, bacteriuria can be due to colonization of the urine or to bacterial contamination of the specimen . There are multiple methods for collecting a urine specimen including: mid‐stream clean catch, mid‐stream urine without cleaning, random sample without instructions, catheterized specimen, or suprapubic aspiration . There is concern that contamination from urethral and vaginal flora can impair the diagnostic reliability of a clean catch sample …”
Section: Discussionmentioning
confidence: 99%